2005
DOI: 10.1111/j.1468-1331.2004.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis and sports: a case–control study

Abstract: An increased incidence of amyotrophic lateral sclerosis (ALS) amongst soccer players in Italy has recently been reported. A case-control study (300 cases and 300 matched controls) was conducted to explore the association between ALS and physical/sports activities, with specific reference to trauma-related risk. Neither the practice of competitive sports nor sports-related traumas were found to be associated with an increased risk of ALS. The practice of physical activities or sports is not per se a risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 12 publications
0
39
2
Order By: Relevance
“…Recently, Chen and colleagues [7] found an association with repeated head injuries or being injured within 10 years before diagnosis. These results were not supported by other studies [1,9,21,28,32] or by our own, in which the higher percentage of head trauma recorded in patients was also without statistical significance.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Recently, Chen and colleagues [7] found an association with repeated head injuries or being injured within 10 years before diagnosis. These results were not supported by other studies [1,9,21,28,32] or by our own, in which the higher percentage of head trauma recorded in patients was also without statistical significance.…”
Section: Discussioncontrasting
confidence: 82%
“…Our results are in keeping with preceding reports showing no relation between smoking and ALS [13,20,28], in contrast with others [1,7,8,10,11,17,19,21,22,26,27,[30][31][32][33][34]. The causal relationship between smoking and the risk of ALS in the aforementioned studies is actually rather unclear, with increasing risk found alternatively in former smokers [19], in current smokers [11,26,31,34] and in women only [34].…”
Section: Discussioncontrasting
confidence: 59%
“…The identification of a very high incidence of ALS among Italian professional footballers [12], and American football players [13], has led to speculation over whether head injury through contact with the football is a relevant explanation. There is conflicting evidence of a more general association between physical fitness and the later development of ALS [14][15][16], and it is plausible that a genetic profile which promotes physical prowess in youth may be deleterious to the ageing motor system [17], rather than exercise per se being detrimental to those at risk for another reason.…”
Section: Introductionmentioning
confidence: 96%
“…However, the etiology of sporadic ALS remains unknown. Many hypotheses on the etiology of ALS have been offered, including exogenous environmental neurotoxins [2][3][4][5][6][7] , heavy metals [8][9][10] , dietary factors [9,[11][12][13][14] , physical exertion or trauma [15,16] , and genetic factors [17,18] . However, the large number of epidemiologic and laboratory studies of ALS have not consistently supported particular causative external factors for development of the disease.…”
Section: Introductionmentioning
confidence: 99%